A solid hydrogen storage material and preparation method thereof
By loading single-atom calcium on graphene, a graphene-loaded single-atom calcium material is prepared, which solves the problem of low hydrogen storage density in graphene and achieves a solid hydrogen storage material with high hydrogen storage density and stability.
Patent Information
- Application Number
- CN202310782661.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-06-29
AI Technical Summary
The existing graphene materials have low hydrogen storage density, mainly because their adsorption intensity with hydrogen molecules is too low, which makes it impossible to effectively increase the hydrogen storage capacity of solid hydrogen storage materials.
The graphene-supported single-atom calcium material was prepared by loading single-atom calcium on graphene, controlling the content of calcium atoms to 0.27 at % and drying in vacuum at 200°C. This method ensures that calcium atoms are distributed evenly and avoids agglomeration through electrostatic adsorption and high-temperature curing.
The hydrogen storage density of graphene materials is improved while maintaining its high specific surface area and stability, significantly improving the hydrogen storage capacity of solid hydrogen storage materials.
Smart Images

Figure CN116639648B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid-state hydrogen storage material and a preparation method thereof, and in particular to a graphene-based single-atom calcium solid-state hydrogen storage material and a preparation method thereof. Background Art
[0002] With the rapid development of economy and society, the demand for energy has also increased dramatically. At present, the main supply of global energy is fossil fuels, accounting for about 85% of the total energy consumption. The combustion of fossil fuels not only produces a large amount of greenhouse gas emissions such as CO2, which affects climate change, but also produces emissions of nitrogen oxides, sulfides, etc., which pollute the environment. Therefore, it is imperative to develop and use green new energy. Among the many new energy sources including wind energy, solar energy, hydrogen energy, ocean energy, bioenergy and geothermal energy, hydrogen energy, with its high fuel value, pollution-free, abundant reserves, wide distribution, and many forms, has become the first choice for the industrialization of global clean energy, and has shown a trend of vigorous development and competition worldwide. However, there is no doubt that in the production, transportation, storage and utilization of hydrogen energy, the biggest key issue is the development of efficient hydrogen storage technology. Among the three existing hydrogen storage methods, including high-pressure gaseous hydrogen storage, low-temperature liquid hydrogen storage and solid-state hydrogen storage, it is obvious that solid-state hydrogen storage has an absolute advantage over high-pressure gaseous and low-temperature liquid hydrogen storage due to its high safety, high theoretical hydrogen storage density and low cost, as it is safer in the future.
[0003] Among solid hydrogen storage materials, high specific surface area carbon materials, such as porous carbon, activated carbon, graphene, carbon nanotubes, etc., have always been a material system that has attracted much attention. On the one hand, this is because carbon materials have economic advantages such as wide sources, low prices, and high cost performance; on the other hand, this is because carbon materials have their own intrinsic hydrogen storage advantages such as high chemical stability, high thermal stability, and large specific surface area. Among carbon materials, two-dimensional graphene materials, in particular, are solid carbon-based hydrogen storage materials that have attracted much attention and have greater hydrogen storage potential. This is because graphene has a large theoretical specific surface area (2630m 2 g -1 ), high thermal stability and chemical stability, and more importantly, a larger modification space. However, although graphene has high hydrogen absorption and desorption cycle stability, its hydrogen storage density has always been relatively low. The main reason is that the adsorption strength of graphene and hydrogen molecules is too low. Therefore, it is urgent to develop a solid hydrogen storage material with large specific surface area, good stability and high hydrogen storage density. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a solid hydrogen storage material with large specific surface area, good stability and high hydrogen storage density and a preparation method thereof.
[0005] The technical solution of the present invention is:
[0006] A solid-state hydrogen storage material is special in that: the solid-state hydrogen storage material is a carbon material in which single-atom calcium is loaded on graphene.
[0007] Furthermore, the content of calcium atoms in the carbon material in which single-atom calcium is supported on graphene is 0.27 at %.
[0008] Furthermore, the monolayer ratio of the graphene is 60%.
[0009] On the other hand, a method for preparing a solid hydrogen storage material comprises the following specific steps:
[0010] (1) Preparation of Ca(NO3)2-graphene dispersion
[0011] Add Ca(NO3)2 and graphene in a mass ratio of 1:50 into deionized water, stir evenly at room temperature, and make the graphene evenly dispersed in the mixed solution to obtain a Ca(NO3)2-graphene dispersion;
[0012] (2) Preparation of graphene-loaded single-atom calcium material
[0013] The Ca(NO3)2-graphene dispersion was allowed to stand at room temperature, the supernatant was removed, and the precipitate was retained to obtain a preliminary product of graphene-supported single-atom calcium material;
[0014] (3) Vacuum drying
[0015] The graphene-supported single-atom calcium material was vacuum-dried at 200° C. for 12 h to obtain the graphene-supported single-atom calcium material.
[0016] Furthermore, the specific surface area of the graphene is 280 m 2 g -1 ~300m 2 g -1 .
[0017] As a further preference, the monolayer ratio of the graphene is 60%.
[0018] Furthermore, the stirring speed is 60 rpm and the stirring time is 12 hours.
[0019] Furthermore, the static aging time is 12 hours.
[0020] Furthermore, the mass volume ratio of Ca(NO3)2 to deionized water is 12:1 mg / L.
[0021] Beneficial effects of the present invention:
[0022] (1) Strictly control the amount of raw material calcium nitrate used, to ensure that the metal calcium atoms are loaded with single atoms, to avoid the agglomeration of metal calcium due to its strong cohesive energy (about 1.8 eV) and dense distribution, to form sub-nanometer-scale clusters or even nanometer-scale grains, and to ensure the loading amount of metal calcium atoms and the hydrogen storage density. Therefore, in the experiment, three different amounts of Ca(NO3)2 were weighed from small to large and diluted into different molar amounts of Ca(NO3)2 in deionized water. 2+ , and then Ca 2+ loaded onto the graphene surface.
[0023] (2) Ca(NO3)2 and graphene are continuously stirred in deionized water. At this time, calcium nitrate Ca(NO3)2, a strong electrolyte, has been fully dissolved in the deionized water to form a uniform Ca(NO3)2 2+ and NO3 - ions, but not soluble in deionized water. However, after sufficient stirring, the graphene dispersed in deionized water can be evenly dispersed and exposed to a larger surface. Therefore, the uniformly dispersed Ca 2+ and NO3 - Because of their electric charge, ions are more likely to be uniformly electrostatically adsorbed on the larger surface area of graphene and evenly dispersed and bonded to the surface of graphene. 2+ and NO3 - After the ionic graphene is fully precipitated, the upper clear liquid is removed, and the remaining precipitate is the initial product of graphene-loaded single-atom calcium material.
[0024] (3) The initial slurry of single-atom calcium-doped graphene was vacuum-dried at 200°C. On the one hand, it was mainly to fully volatilize the H2O molecules and then dry the sample. On the other hand, it was mainly to high-temperature solidify the metal calcium (Ca) single atoms chemically adsorbed on the graphene.
[0025] (4) Graphene-loaded single-atom calcium material is a material in which single alkaline earth metal calcium (Ca) atoms are loaded on graphene. With the help of the strong interaction between calcium metal atoms and hydrogen molecules, it not only maintains the characteristics of graphene's large specific surface area and good stability, but also effectively improves the hydrogen storage capacity of graphene. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The double spherical aberration transmission electron microscope photographs of the graphene-supported single-atom calcium material prepared in the present invention (corresponding to Example 1, Comparative Example 1 and Comparative Example 2);
[0027] Figure 2 X-ray diffraction pattern of graphene-supported single-atom calcium material prepared in the present invention (corresponding to Example 1);
[0028] Figure 3The full spectrum of the X-ray photoelectron spectrum of the graphene-supported single-atom calcium material prepared in the present invention (corresponding to Example 1);
[0029] Figure 4 This is a scanning electron microscope image of the graphene-supported single-atom calcium material prepared in the present invention (corresponding to Example 1);
[0030] Figure 5 The energy spectrum of the graphene-supported single-atom calcium material prepared in the present invention (corresponding to Example 1) is obtained by scanning electron microscopy;
[0031] Figure 6 The graphene-supported single-atom calcium material prepared in the present invention (corresponding to Example 1) is tested for changes in hydrogen absorption and desorption performance at liquid nitrogen temperature (77K) accompanied by changes in pressure (0-50bar);
[0032] Figure 7 The graphene raw material of Example 1 of the present invention is tested for its hydrogen absorption and desorption curve performance at liquid nitrogen temperature (77K) with pressure changes (0-50bar). DETAILED DESCRIPTION
[0033] Example 1
[0034] (1) Preparation of Ca(NO3)2-graphene dispersion
[0035] Weigh 6 mg of calcium nitrate Ca(NO3)2 and mix with 300 mg of graphene, the graphene has a monolayer rate of 60% and a specific surface area of 300 m 2 g -1 , then pour into 500mL of deionized water and mix evenly to dilute;
[0036] The mixture was stirred at 60 rpm for 12 hours. At the beginning of the stirring process, the mixed liquid had visible graphene clusters. With the continuous stirring time, the visible graphene clusters had become a uniformly dispersed black mixed liquid. Although graphene is insoluble in deionized water, it has become a uniformly mixed black Ca(NO3)2-graphene dispersion liquid by macroscopic observation.
[0037] (2) Preparation of graphene-loaded single-atom calcium material
[0038] The Ca(NO3)2-graphene dispersion was allowed to stand at room temperature for 12 hours, the supernatant was removed, and the precipitate was retained to obtain a preliminary product of graphene-supported single-atom calcium material;
[0039] (3) Vacuum drying
[0040] The graphene-supported single-atom calcium material was vacuum-dried at 200° C. for 12 h to obtain the graphene-supported single-atom calcium material.
[0041] Figure 1 (a) is a double spherical aberration transmission electron microscope photo of the graphene-supported single-atom calcium material prepared in Example 1 of the present invention. Obviously, Figure 1 In (a), the single-atom calcium is evenly distributed without any agglomeration, as shown by the white bright spot in the dotted circle, which is the single-atom calcium.
[0042] Figure 2 From the X-ray diffraction pattern of the graphene-loaded single-atom calcium material prepared in Example 1 of the present invention, it is not difficult to find that this is the diffraction peak of pure carbon, but there is no diffraction peak of Ca atomic nanoparticles and other crystal peaks, which once again proves that the prepared composite material is single-atom calcium-loaded rather than nanoclusters or nanocrystals.
[0043] Figure 3 The full spectrum of the X-ray photoelectron spectrum of the graphene-loaded single-atom calcium material prepared in Example 1 of the present invention shows that the presence and relative contents of C, N, O and Ca elements are C (88.84 at%), N (1.4 at%), O (9.49 at%) and Ca (0.27 at%), respectively. This proves the successful loading of Ca atoms on the one hand, and on the other hand, proves that the relative content of calcium atoms is relatively low when they exist in the form of single atoms.
[0044] Figure 4 From the scanning electron microscope image of the graphene-loaded single-atom calcium material prepared in Example 1 of the present invention, it is not difficult to find that the graphene composite material loaded with single-atom calcium still maintains the morphological characteristics of pure graphene.
[0045] Figure 5 The SEM spectrum of the graphene-loaded single-atom calcium material prepared in Example 1 of the present invention shows, on the one hand, that the distribution of different elements is uniform, and on the other hand, that the relative contents of different elements are consistent with the content variation trends of the X-ray photoelectron spectrum.
[0046] Figure 6 The graphene-loaded single-atom calcium material prepared in Example 1 of the present invention was tested for changes in hydrogen absorption and desorption performance at liquid nitrogen temperature (77K) accompanied by changes in pressure (0-50 bar), and it was found that it had good hydrogen absorption and desorption performance.
[0047] Figure 7 The hydrogen absorption and desorption curve test of the raw material graphene used in Example 1 of the present invention was carried out under the same conditions, that is, the change of hydrogen absorption and desorption performance under liquid nitrogen temperature (77K) accompanied by the change of pressure (0-50bar). It was found that compared with the performance of graphene-supported single-atom calcium material (such as Figure 6), unstable hydrogen absorption and desorption performance appeared, which was mainly manifested in the cross stability of hydrogen absorption and desorption curves, which may be caused by the material's own structure and functional groups.
[0048] Example 2
[0049] The electromagnetic stirring speed was changed, and the other parts were the same as in Example 1. The electromagnetic stirring speed was set at a lower speed (30 rpm) resulting in a stratification phenomenon of the black mixed solution with a clear upper part and a turbid lower part, and a higher speed (90 rpm) resulting in a vortex in the center of the beaker to centrifuge the mixed solution to an area closer to the beaker wall, both resulting in uneven mixing.
[0050] Comparative Example 1
[0051] (1) Preparation of Ca(NO3)2-graphene dispersion
[0052] Weigh 12 mg of calcium nitrate Ca(NO3)2 and mix with 300 mg of graphene, the graphene has a monolayer rate of 60% and a specific surface area of 300 m 2 g -1 , then poured into 500 mL of deionized water to mix and dilute evenly, and fully electromagnetically stirred at 60 rpm for 12 hours to obtain a black Ca(NO3)2-graphene dispersion;
[0053] (2) Preparation of graphene-loaded calcium material
[0054] The Ca(NO3)2-graphene dispersion was allowed to stand at room temperature for 12 hours, the supernatant was removed, and the precipitate was retained to obtain a preliminary product of graphene-loaded calcium material;
[0055] (3) Vacuum drying
[0056] The graphene-loaded calcium material was vacuum-dried at 200° C. for 12 h to obtain the graphene-loaded calcium material. Figure 1 (b) is a double spherical aberration transmission electron microscope photo of the graphene-loaded calcium material prepared in Comparative Example 2 of the present invention. Figure 1 (b) It can be seen that clusters appear in the figure, just like the white bright spots in the dotted circle in the figure, which are clusters formed by several to dozens of calcium atoms.
[0057] Comparative Example 2
[0058] (1) Preparation of Ca(NO3)2-graphene dispersion
[0059] Weigh 18 mg of calcium nitrate Ca(NO3)2 and 300 mg of graphene, the graphene has a monolayer rate of 60% and a specific surface area of 300 m 2 g -1, then poured into 500 mL of deionized water to mix and dilute evenly, and fully electromagnetically stirred at 60 rpm for 12 hours to obtain a black Ca(NO3)2-graphene dispersion;
[0060] (2) Preparation of graphene-loaded calcium material
[0061] The Ca(NO3)2-graphene dispersion was allowed to stand at room temperature for 12 hours, the supernatant was removed, and the precipitate was retained to obtain a preliminary product of graphene-loaded calcium material;
[0062] (3) Vacuum drying
[0063] The graphene-loaded calcium material was vacuum-dried at 200° C. for 12 h to obtain the graphene-loaded calcium material. Figure 1 (c) is a double spherical aberration transmission electron microscope photo of the graphene-loaded calcium material prepared in Comparative Example 2. Figure 1 (c) It can be seen that more agglomerations appear in the figure, as shown by the white part circled in the dotted circle.
[0064] Example 1, Comparative Example 1 and Comparative Example 2 were tested in parallel with different calcium nitrate addition amounts. Only Example 1 obtained a better single atom distribution, otherwise clusters or even nanocrystals would appear. Figure 1 It can be seen that if the single atom weight of loaded calcium (Ca) exceeds the critical value, the single atoms of calcium (Ca) will agglomerate due to the strong cohesive energy (about 1.8 eV) and dense distribution, and then form sub-nanometer clusters or even nanometer-scale grains, and single-atom hydrogen storage materials cannot be prepared. However, the reduction in the amount of metal atoms loaded will result in a decrease in hydrogen storage density. The purpose of improving the hydrogen storage performance of carbon materials cannot be achieved. Therefore, the content of calcium atoms in the carbon material loaded with single-atom calcium on graphene is 0.27at%, which can be used as an excellent solid-state hydrogen storage material.
[0065] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A solid hydrogen storage material, characterized in that: The solid-state hydrogen storage material is a carbon material in which single-atom calcium is loaded on graphene. The content of calcium atoms in the graphene is 0.27 at%, the monolayer rate of the graphene is 60%, and the specific surface area of the graphene is 300 m 2 g -1 ; The preparation steps of the solid-state hydrogen storage material are as follows: (1) Preparation of Ca(NO3)2-graphene dispersion Ca(NO3)2 and graphene were added into deionized water in a mass ratio of 1:50, and stirred evenly at room temperature to make the graphene evenly dispersed in the mixed solution to obtain a Ca(NO3)2-graphene dispersion; (2) Preparation of the initial product of graphene-loaded single-atom calcium material The Ca(NO3)2-graphene dispersion was allowed to stand at room temperature, the supernatant was removed, and the precipitate was retained to obtain a preliminary product of graphene-supported single-atom calcium material; (3) Vacuum drying The graphene-supported single-atom calcium material was vacuum-dried at 200° C. for 12 h to obtain the graphene-supported single-atom calcium material.
2. The solid hydrogen storage material according to claim 1, characterized in that: The stirring speed was 60 rpm and the stirring time was 12 h.
3. The solid hydrogen storage material according to claim 1, characterized in that: The resting time is 12 hours.
4. The solid hydrogen storage material according to claim 1, characterized in that: The mass volume ratio of Ca(NO3)2 to deionized water is 12:1 mg / L.